RISK MANAGEMENT IN ISLAMIC FINANCIAL TECHNOLOGY - Umari Abdurrahim Abi Anwar; Megha Sakova; Ikin Solikin; Asni Mustika Rani (STIE PGRI Dewantara Jombang, 2022)
Digital developments have encouraged the development of financial technology (fintech) companies in the world, including fintech that upholds sharia principles. Until 2022, there are only seven sharia fintech companies registered with the Financial Services Authority (FSA/OJK) in Indonesia. Awareness of sharia products/services is still very small and tends to grow slowly. One way to catch up with Islamic fintech is to manage risk management. This is important to provide safe and comfortable services for consumers. The purpose of this study is to describe risk management and risk mitigation in Islamic fintech. This research is a literature study using secondary data in the form of journal articles published in reputable international journals. From the research results it is known that the importance of implementing risk management in Islamic fintech is closely related to technology risk. After all, the system is a media platform with connected hardware and software using the internet as an open trading system. The application of technology risk management needs to be adjusted to the objectives and policies of the digital financing business strategy (complexity).